Melawan Konstruksi Sosial dan Budaya Terhadap Perempuan: Mewujudkan Keadilan Gender dalam Rumah Tangga - Yulianti Yulianti; Ummi Ulfatus Syahriyah (UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. There is a social and cultural construct in society that put a mother as the most responsible person for childcare. In fact, childcare is basically a shared responsibility between husband and wife. Although mothers are the first school for their children, fathers also have a great responsibility in childcare. Not only given great responsibility in childcare, social and cultural constructions in Indonesia form that a wife or mother must be able to do housework and the husband is responsible for providing a living. The purpose of this study, researchers want to see how a mother eliminates the constructions that develop in society in realizing gender justice and equality in the household. The research method in this study is a descriptive qualitative method because it is to discuss the research results comprehensively. Data collection in this study used interviews with two young mothers. The results in this study show that in realizing gender justice in the household, each couple must prepare for marriage in terms of science and mentality so that each other understands each other regarding their respective roles and responsibilities. responsible for childcare and domestic work. And the establishment of a culture of communication in carrying out the division of roles in order to the emergence of justice in the household. Keywords: Construction, Women, Gender Justice. Abstrak. Ada konstruksi sosial dan budaya di masyarakat yang beranggapan seorang ibu adalah orang paling bertanggung jawab dalam pengasuhan anak. Padahal, pada dasarnya pengasuhan anak adalah tanggung jawab bersama antara suami dan istri. Meskipun ibu adalah sekolah pertama bagi anak-anaknya, ayah juga memiliki tanggung jawab besar dalam pengasuhan anak. Kemudian, ibu tidak hanya diberikan tanggung jawab besar dalam pengasuhan anak, konstruksi sosial dan budaya di Indonesia juga meletakkan seorang istri atau ibu dalam pekerjaan rumah tangga dan suami bertanggung jawab untuk mencari nafkah. Penelitian ini bertujuan melihat bagaimana seorang ibu menghilangkan konstruksi yang berkembang di masyarakat dalam mewujudkan keadilan gender dan kesetaraan dalam rumah tangga. Penelitian ini menggunakan metode kualitatif deskriptif karena membahas hasil penelitian secara komprehensif. Pengumpulan data dilakukan dengan wawancara dengan dua ibu muda. Hasilnya menunjukkan bahwa dalam mewujudkan keadilan gender dalam rumah tangga, setiap pasangan harus mempersiapkan pernikahan dari segi ilmu pengetahuan dan mental agar saling memahami peran dan tanggung jawabnya masing-masing. Bertanggung jawab atas pengasuhan anak dan pekerjaan rumah tangga. Dan terbentuknya budaya komunikasi dalam melaksanakan pembagian peran demi munculnya keadilan dalam rumah tangga. Kata Kunci: Konstruksi, Perempuan, Keadilan Gender.